Penghijauan Untuk Meningkatkan Semangat dan Motivasi Belajar Santri di Pondok Pesantren Darullughah Wadda’wah - Nurul Fauzah (Filantropis: Jurnal Pengabdian kepada Masyarakat, 2025)
The limited vegetation, high temperatures, and absence of green spaces in many Islamic boarding schools (pesantren) contribute to students’ cognitive fatigue, stress, and declining learning motivation. These conditions are further intensified by the demanding daily routines of santri, who require restorative environments to support their psychological well-being. This community engagement program aims to enhance comfort, motivation, and mental health among santri through a greening initiative employing a participatory empowerment approach. The program was implemented using the participatory action research (PAR) method, involving planning, training, planting activities, ongoing assistance, maintenance, and evaluation, with active participation from caregivers, administrators, and students. The results show that the greening activities improved the pesantren’s physical environment, reduced ambient temperature and dust levels, and created new green communal spaces utilized for informal learning. Beyond ecological improvements, the program significantly increased students’ learning motivation, academic discipline, and psychological comfort, strengthened by the integration of Islamic values related to environmental stewardship. The contribution of this program lies in offering an integrative model of greening that combines ecological practices with spiritual and educational values, providing a foundation for the long-term development of sustainable eco-pesantren.